Mapping Tourism Potential Based on Urban Heritage Tourism in Medan City - Ponirin; Tappil Rambe; Leylia Khairani (CSR International Journal, 2021)
The city of Medan is the third-largest city in Indonesia and has historical buildings or heritage that can be revitalized as a cultural heritage with tourism potential that can be developed. However, until now, the colonial heritage buildings have been destroyed up to 70%. This research method uses a tourism anthropology approach with a qualitative research type that focuses on tourist destinations. The research location is a heritage area, a colonial heritage building in the Merdeka Square segment, Maimoon segment, Benteng segment, Youth segment, Polonia segment, and Sambu segment. The study results reveal that Medan has a heritage in the form of historic buildings that have the potential to be developed and represent the identity of the city of Medan. The potential for tourism development can be carried out in 3 (three) potential areas, namely: 1) The youth segment, which includes Gedung Juang 45, which currently functions as the Sumatran Money Museum, Tip Top Restaurant, and Tjong A Fie Mansion. 2) the Maimoon segment, which includes: Maimoon Palace and the Great Mosque. 3) The Merdeka Square segment includes City Hall, which currently functions as the Grand City Hall, Hotel De Boer (currently called Grand Inna Hotel), and the London Sumatra building. Through urban tourism based on urban heritage tourism, tourists can be invited to appreciate and interpret the objects observed. It serves as education and recreation for the community. This activity is also a means of preserving the wealth and identity of the city of Medan.